2018
DOI: 10.3389/fphys.2018.00937
|View full text |Cite
|
Sign up to set email alerts
|

Blood Gene Expression and Vascular Function Biomarkers in Professional Saturation Diving

Abstract: Saturation diving is an established way to conduct subsea operations with human intervention. While working, the divers must acclimatize to the hyperbaric environments. In this study, genome-wide gene expression and selected plasma biomarkers for vascular function were investigated. We also examined whether antioxidant vitamin supplements affected the outcome. The study included 20 male professional divers, 13 of whom took vitamin C and E supplements in doses of 1,000 and 30 mg daily during saturation periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…ROS are usually associated with damages and negative consequences exerted on cells but are also involved in several protective mechanisms, such as immune defense, antibacterial action, vascular tone regulation, and signal transduction [ 29 ]. Moreover, a recent research study [ 17 ] demonstrated that differential gene expression indicated reduced blood O 2 transport and increased endogenous antioxidant activity after saturation diving. During prolonged exposure to a confined, hyperbaric, hyperoxic environment, antioxidant supplementation is recommended for saturation divers to reduce oxidized molecules [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are usually associated with damages and negative consequences exerted on cells but are also involved in several protective mechanisms, such as immune defense, antibacterial action, vascular tone regulation, and signal transduction [ 29 ]. Moreover, a recent research study [ 17 ] demonstrated that differential gene expression indicated reduced blood O 2 transport and increased endogenous antioxidant activity after saturation diving. During prolonged exposure to a confined, hyperbaric, hyperoxic environment, antioxidant supplementation is recommended for saturation divers to reduce oxidized molecules [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant defenses are known to increase when the production of ROS is enhanced [ 7 , 15 , 16 ]. Additionally, the administration of antioxidant and vitamin supplements is an intuitive measure to boost antioxidant defenses against ROS [ 17 ]. Recent literature has demonstrated that differential gene expression indicated reduced blood O 2 transport and increased endogenous antioxidant activity after saturation diving.…”
Section: Introductionmentioning
confidence: 99%
“…In our setting, it is very complicated to set direct links between pulmonary and neurological oxygen toxicity from a clinical point-of-view. Nevertheless, we indirectly relied on actual data showing that the cellular reactions in healthy subjects undergoing a prolonged higher oxygen inspired fraction recover faster (in the first 24 h) and show no permanent damage, as shown from saturation studies (particularly on the decompression phase where the FiO2 is higher for several days) through the erythropoietin rebound reaction [58,59]. Furthermore, intermittent oxygen exposure in laboratory animals has been shown to be beneficial on tumor suppression with or without adjuvant chemotherapy [4,26,60].…”
Section: Oxygen Toxicitymentioning
confidence: 99%
“…Indeed, the difference in conditions between dry and wet dives ( Weathersby et al, 1990 ), including the use of hot-water suits ( Hope et al, 2005 ) and the activity level during the dive; contribute to the stress levels faced during the dives ( Møllerløkken et al, 2011 ). In a previous study of commercial saturation divers on the Norwegian Continental Shelf, the divers’ hematocrit levels were measured ( Kiboub et al, 2018 ). Data showed they were reduced post-surfacing, a possible sign of physiological acclimatization to an elevated partial pressure of oxygen (ppO 2 ) during saturation.…”
Section: Introductionmentioning
confidence: 99%